In search of security: The migration conundrum and the need for a global response - Angelo Martelli (EconPol Forum, 2025)
Security is simultaneously the foremost concern for citizens in destination countries, who feel threatened by migrants and refugees and call on their leaders to regain control by erecting barriers and closing borders, and also the driving force behind migratory flows. There is a protracted inability to move from a crisis management situation to a sustainable global governance of migration. Is the EU's New Pact on Migration and Asylum a historic agreement or a broken deal?. There is a need to go beyond the lump of labor fallacy and emphasize the net contribution of migration through enhanced integration and social cohesion. A successful migration strategy must be multifaceted, targeting both the root causes of displacement and its effects on displaced individuals and host communities.
Keywords: 330